Effect of 6-week single leg countermovement jump training on force time metrics in elite female youth footballers - Fahey, J. T.; Comfort, P.; Jones, P.; Ripley, N. J. (Journal of Sports Sciences, 2025)
Female football participation has grown exponentially. Unfortunately, females exhibit greater injury risk than male athletes, and experience increased mechanical stress during adolescence. Force plates provide accurate and reliable force-time characteristics enabling profiling of injury risk and benchmarking using a variety of jump and isometric tasks. The purpose of this study was to determine whether test-retest reliability and force-time characteristics of SLCMJ, bilateral countermovement jump (CMJ), countermovement rebound jump (CMJ-R) and isometric mid-thigh pull (IMTP) change with six weeks of SLCMJ training. Twenty-eight elite youth female footballers (13.7 ± 1.1 years, 53.27 ± 8.82 kg, 162.20 ± 5.37 cm) completed six weeks of SLCMJ as part of a routine strength and plyometric training program. SLCMJ training did not influence test-retest reliability and resulted in favourable adaptations indicated through small to large changes in force-time characteristics for SLCMJ. Significant (p < 0.05) yet trivial to small favourable changes were observed for the CMJ and CMJ-R, with small increases observed for IMTP. The results of this study demonstrate that six weeks of SLCMJ training does not influence phase-specific test-rest reliability (i.e. braking and propulsion) and causes weekly fluctuations in force-time characteristics leading to im.provements in SLCMJ, CMJ, CMJ-R and IMTP. Practitioners can use such information to inform training design and monitor athlete performance